Molecular Biologic Milieu in Rhegmatogenous Retinal Detachment and Proliferative Vitreoretinopathy: A Literature Review - Ananikas,K.; Stavrakas,P.; Kroupis, C.; Christou,E.E.; Brouzas,D.; P. Petrou; Papakonstantinou,D. (Ophthalmic Res., 2022)
Multiple lines of evidence support an immunologic response along with inflammation to be implicated in the pathophysiology of primary rhegmatogenous retinal detachment (RRD) and the development of proliferative vitreoretinopathy (PVR). The purpose of this review is to provide an update on the signaling molecules in the vitreous and subretinal fluid (SRF) involved in these processes. A detailed literature search was performed in PubMed database until November 2021. We identified all papers referring to inflammatory and immunological mediators in the context of primary RRD and in cases complicated by PVR. We analyzed prospective and retrospective cohort studies and reference lists of the retrieved articles. A comprehensive investigation of immunological and inflammatory responses provides significant evidence for the implication of varying signaling molecules in the pathophysiology of RRD and the development of PVR. The reviewed series has revealed that disruption of the normal equilibrium during these processes may be present in the vitreous and SRF of these eyes. The precise role of cytokines, chemokines, and growth factors in the pathophysiology of these disorders remains to be clearly elucidated. Overall, immunological and inflammatory signaling molecules are widely implicated in both primary RRD and PVR. The reviewed literature indicates that precise knowledge concerning the pathological milieu sheds light on the underlying pathophysiology and potential therapeutic targets and highlights unmet needs to be addressed by future research
Keywords: Humans; Prospective Studies; Retinal Detachment; Retrospective Studies